Steroid transnasal nebulization in the treatment of chronic rhinosinusitis. Issue 1 (February 2016) - Lou, Hongfei; Wang, Chengshuo; Zhang, Luo
Abstract : Purpose of review: Chronic rhinosinusitis (CRS) is a challenging disease entity, affecting 8–15% of the general population. Topical steroids have been recommended as an integral part of the strategy for management of CRS. This review focuses on steroid transnasal nebulization as an alternative treatment option for CRS treatment. Recent findings: Modern inhalation devices comprise nebulizers, pressurized metered-dose inhalers and dry powder inhalers. Transnasal nebulization with pulsating flow can enhance sinus ventilation and increase drug deposition with longer residence time. Short-term steroid transnasal nebulization provides an effective and safe treatment option for CRS patients, as evidenced by significant clinically relevant improvements and lack of serious side-effects. The underlying mechanisms involve a combination of reduction in inflammatory cells, suppression of inflammatory cell-associated cytokines and chemotactic factors, and regulation of tissue remodeling. Efficacy of transnasal nebulization outweighs commonly used nasal sprays and nasal irrigation as delivery options for topical steroids; however, long-term safety with nebulized steroids needs to be investigated further. Summary: Steroid transnasal nebulization offers an alternative or a complementary treatment option to nasal sprays and nasal irrigation for management of patients with CRS. Long-term dose-dependent studies with nebulized steroids will be needed to fully appreciate the benefits of this treatment modality.